Competências multiculturais e global mindset: um estudo de caso na empresa Sap Labs Latin America - Orth, Silvana Beatriz (Universidade do Vale do Rio dos Sinos, 2017)
This study aims to present how Global Mindset's multicultural competencies become relevant to SAP Labs Latin America employees. In order to achieve this goal, we identified the concepts of multicultural competencies and Global Mindset, in addition to the current practices applied by the company. Through a case study documents made available by the company were analyzed, as well as simple observation and semi-structured interviews. Using the analysis of discourse was possible to identify the characteristics of the interviewees and to obtain answers related to the theory of the main authors of each subject of this study. It was possible to realize that the interviewed professionals have advanced multicultural competencies, since they easily develop activities with people from other cultures in their daily activities, although the development of these competencies is a continuous work. It was verified that there is a very rich source regarding multicultural competencies and Global Mindset in the analyzed company, and these can be found in trainings, pages of internal sites or through tacit knowledge. At the end of the study it was realized that the interviewees are aware that a global leader needs to develop all the Global Mindset capitals, but it is believed that there is a lack of communication by the company to make employees aware of existing tools, which have valuable information that would improve the relationships and execution of activities.
Keywords: Internacionalização; Globalização; Competências; Multiculturalidade; Global Mindset; Internationalization; Globalization; Multicultural Competencies; Global Mindset